2017
DOI: 10.1183/13993003.02552-2016
|View full text |Cite
|
Sign up to set email alerts
|

Automaticversusmanual oxygen administration in the emergency department

Abstract: Oxygen is commonly administered in hospitals, with poor adherence to treatment recommendations.We conducted a multicentre randomised controlled study in patients admitted to the emergency department requiring O ≥3 L·min Patients were randomised to automated closed-loop or manual O titration during 3 h. Patients were stratified according to arterial carbon dioxide tension ( ) (hypoxaemic ≤45 mmHg; or hypercapnic >45-≤55 mmHg) and study centre. Arterial oxygen saturation measured by pulse oximetry ( ) goals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
73
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 33 publications
5
73
2
2
Order By: Relevance
“…Its safety and efficacy for increasing the time spent in the target SpO 2 range have been reported in adults. [19][20][21][22] A recent study showed that FreeO2 technology could be more cost-effective than manual oxygen administration, reducing the per-patient costs over 180 days in an adult population with chronic obstructive pulmonary disease (COPD). 23 In the present study, we aimed to examine the safety of the FreeO2 device-an automated closed-loop O 2 titration technologyand its efficacy for maintaining SpO 2 within a target zone during AHRD in infants and children.…”
Section: Introductionmentioning
confidence: 99%
“…Its safety and efficacy for increasing the time spent in the target SpO 2 range have been reported in adults. [19][20][21][22] A recent study showed that FreeO2 technology could be more cost-effective than manual oxygen administration, reducing the per-patient costs over 180 days in an adult population with chronic obstructive pulmonary disease (COPD). 23 In the present study, we aimed to examine the safety of the FreeO2 device-an automated closed-loop O 2 titration technologyand its efficacy for maintaining SpO 2 within a target zone during AHRD in infants and children.…”
Section: Introductionmentioning
confidence: 99%
“…In an era of precision medicine, the current study published in the ERJ [24] confirms the efficacy of this automated closed loop inspiratory oxygen fraction system for adults with acute respiratory failure, and suggests a "one size fits all" approach may no longer be supported. Long-term studies with other clinical outcomes and cost-benefit analyses are warranted.…”
mentioning
confidence: 76%
“…This study leaves some potential unanswered questions: Does the system described by L'HER et al [24] have the same performance with different interfaces (the face mask used here versus the nasal cannula in their previous studies [23])? Is the oximeter used sensitive enough to correct artefactual causes of hypoxaemia (like low perfusion and motion)?…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…A least one system is FDA-cleared. 88 Lellouche and colleagues [91][92][93][94] have generated much of this work, using a system known as FreeO 2 . They demonstrated efficacy and greater duration of time in desired saturation ranges compared with traditional oxygen therapy during exercise, during COPD exacerbations, and in emergency care.…”
Section: Closed-loop Control Of Oxygen At Homementioning
confidence: 99%